RENCANA BISNIS PETERNAKAN BIBITAYAM SUPER "PARTHACHICK FARM" - , Setiyo Birowo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The livestock sector in realizing the role resilience and food security, especially in food of animal origin.Chicken meat is the top choice of consumers in the fulfillment of animal protein, because the price of chicken meat is relatively cheaper than the price of meat from other animals. Lifestyle return to natural products will also help increasing the product range chicken. Consumer confidence in the natural and healthy eating eggs or chicken meat is increasing its economic value. Consumers believe that the chicken products because of the lack of interference created synthetic chemicals. Delicious and savory taste of chicken has outperformed the chicken meat. Raising native chicken major obstacles that growth tends to be slower when compared to the broiler.With the new technology, now comes the super chicken or chicken java super. Java super chicken or chicken is often called the latest joper derived from crosses involving livestock latest technology to obtain rapid growth and has the characteristics of meat and chicken form. Java super chicken business so super provide new business opportunities in the field of chicken farms. Poultry farm Java Super business plan using the functional strategies and business plans with attention to risk and environmental impact analysis that will be happening in this business. The company will set up a farm in D.I. Yogyakarta, in regions D.I. Yogyakarta, Java super chicken business is relatively new, so players in this business is not so much. The business will be run later using the company name Parthachick Farm. Company revenue derived from the production and sale of seeds or DOC ( Day Old Chicken ) super java chicken. Consumers are becoming the main focus of the company is enlarging chicken farm or a local chicken. Shown in three business scenarios that demonstrate financial performance for a period of 5 years with a variety of assumptions . In the optimistic scenario, obtained Rp 635 317 728 NPV, IRR of 77 % and a discounted payback period of 14.68 months . In a normal scenario, the NPV obtained Rp. 308 732 992 ,an IRR of 54 % and Discounted Payback Period 19.72 a month . In the pessimistic scenario obtained NPV ( USD 561 575 439 ) , an IRR of 0 % and Discounted Payback Period 236.52 a month. With all three scenarios, the expected visible opportunity as well as a more measurable risk of this business.